DUKKU AND BAEKAM SPRINGWATER INHIBIT THE UREASE ACTIVITY OF HELICOBACTER PYLORI - Choi, SungSook; Lee, HaeKyung; Kim, JinWoo; Yu, JiHan; Choi, HyunHo; Kim, HyungKeun; Kim, SangWoo; Chae, Hiun Suk (African Journal of Traditional, Complementary and Alternative Medicines, 2019)
Background: Springwater (SW) contains many kinds of minerals such as sodium, potassium and copper. These metallic ions may influence the activity of metallo-enzymes such as urease via competitive inhibition. In this study, we investigated the effect of SW on the inhibition of Ni-containing urease activity, which is essential for the colonization of Helicobacter pylori (H. pylori) in the human stomach. Materials and Methods: We studied the growth inhibition of H. pylori by SW. We evaluated ammonia production to detect urease activity and performed western blot analysis of UreA and UreB for enzyme production. Results: SW had no significant effect on bacterial growth. Western blot analysis also showed that SW did not affect the translation of UreA and UreB, but it significantly reduced the urease activities of the Jack bean as well as that of H.pylori from 50 to 75%. Conclusion: These results might indicate that the consumption of SW may prevent the colonization of H. pylori andameliorate the toxic effect on gastric mucosa via the inhibition of urease activity.